Diagnostic Analysis of a Production and Distribution System - Hax, Arnoldo C.; Majluf, Nicolas S.; Pendrock, Mark (Management Science, 1980)
This paper reports on a diagnostic study completed by a large firm in the consumer goods sector. This study is aimed at evaluating the production and distribution planning system, the quality of the forecasting system, and the existing levels of inventory. Aggregate models are presented to assess opportunities for improvements in those areas. A proposal for the design of a new production and distribution system, that follows a hierarchical approach, is reviewed. Recommendations for managerial actions are discussed.